(untitled) (Journal of Informatics Education and Research, 2024)
In the era of Omni channel retailing, consumers are spoilt for choices. They may adopt different channels for information search and purchase. Webrooming is searching for information online and ending up purchasing the product offline whereas Showrooming is searching for information offline and ending up with the purchase online. Showrooming will benefit the online sellers while Webrooming benefits the offline stores. Many retailers are going Omni channel in order to take benefit of these shopping behaviours. This research paper focuses on identifying whether the consumer exhibits Webrooming or Showrooming behaviour in the context of mobile phone purchase. The study also compares the purchase behaviour across the age and gender. Empirical study is carried out in Karnataka with a sample of 200 consumers spanning Gen Y and Gen Z. Data collection is both secondary and primary. Quota sampling is used to get primary data from both the Gen Y & Gen Z responses equally. The findings of the study will help the mobile phone manufacturers to plan their retail strategy. Also, this study will help in identifying whether the behaviour of the consumers varies between the different generations and this insight may be used for promoting the products among the different generations.